2022
DOI: 10.3748/wjg.v28.i9.933
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based differences in histology, staging, and prognosis among 2983 gastric cancer surgery patients

Abstract: BACKGROUND Few studies have been conducted on sex differences in the incidence, pathophysiology, and prognosis of gastric cancer (GC). AIM To analyze the differences in GC characteristics according to sex in patients who underwent surgical treatment for GC. METHODS A total of 2983 patients diagnosed with gastric adenocarcinoma who received surgical treatment at the Seoul National University Bundang Hospital between 2003 and 2017 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Female gastric cancer patients had a better prognosis, and this fnding was consistent with most previous studies [9][10][11][12][13][14][15][16][17][18]. Tere are many possible reasons for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Female gastric cancer patients had a better prognosis, and this fnding was consistent with most previous studies [9][10][11][12][13][14][15][16][17][18]. Tere are many possible reasons for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
“…Figure 2 presents the meta-analysis of the 3-year overall survival (OS) and 5-year OS in the total patient population reviewed. Significant sex-based differences in the OS of the total patient population obtained from the twenty-eight studies reviewed were found [ 9 16 , 19 24 , 31 , 45 , 55 , 61 , 65 , 69 72 , 80 , 81 , 86 , 87 , 89 ]. Our meta-analysis showed that females with gastric cancer were associated with better 3-year OS and 5-year OS relative to males (HR = 0.90, 95% CI: 0.86, 0.95, P = 0.003, I 2 = 53%; HR = 0.86, 95% CI: 0.82, 0.91, P < 0.00001, I 2 = 66%,respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, diffuse-type GC was more frequent in females (86.4%) than in males (76.6%).These results were also found in previous reports of GC patients receiving surgical treatment, with diffuse-type GC common in young females, and females had a poor prognosis than males in the advanced TNM stage group. 27 However, BMI information was not included in the report. Above all, we highlighted the sex differences in the association between BMI and GC location, treatment modality, TNM stage, and tissue type, that is, a higher proportion of patients with severe obesity (9.3%) was found only in males but not in females (3.6%).…”
Section: Discussionmentioning
confidence: 99%